/s/-Lenition and the Preservation of Plurality in Modern Occitan1. Issue 2 (24th October 2014) - MacKenzie, Laurel
Abstract : This paper examines the variable weakening and deletion of /s/ in the Languedocian variety of Modern Occitan, with particular attention to how it has affected the system of plural marking in noun phrases. Using data from linguistic atlases, I demonstrate that /s/-lenition in this variety involves a stage of vocalization to [j]. I find that, where /s/ on the definite article has vocalized to [j], the immediately-preceding vowel of the definite article has undergone concomitant raising to [e]. This raising appears to preserve the difference between singular and plural despite the plural's weakening /s/. I argue that these results support Labov's (1994 ) hypothesis that the meaning of a weakening element may be transferred to a stable, co-occurrent one.